FINANCIAL PERFORMANCE AND ENVIRONMENTAL PERFORMANCE IN COMPANY DISCLOSURES OF CORPORATE SOCIAL RESPOSIBILITY - Yanti, Novi; Yunan, Nadiya (Universitas 17 Agustus 1945 Surabaya, 2024)
This study aims to analyze the effect of financial performance and environmental performance on Corporate Social Responsibility (CSR) disclosure. In the era of the industrial revolution 4.0, companies are required to increase productivity through the use of advanced technology, but often ignore social and environmental responsibilities that have an impact on ecosystem damage and social conflict. Based on Law No. 40 of 2007 and Law No. 25 of 2007 in Indonesia, companies are required to carry out social and environmental responsibilities. This study uses a quantitative approach with a sample of mining companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2022 period. The data analysis techniques used are multiple linear regression and moderated regression. The variables analyzed include profitability, leverage, company size, and environmental performance. The results of the study show that leverage and environmental performance have an effect on CSR disclosure, while profitability and company size have no effect. These findings indicate that companies with good financial performance do not always prioritize CSR disclosure, and that good environmental performance is more likely to encourage broader CSR disclosure. This study provides an important contribution to understanding the factors that influence CSR disclosure and how companies can improve their transparency and accountability to stakeholders